1895
DOI: 10.1002/cber.189502802159
|View full text |Cite
|
Sign up to set email alerts
|

Ueber die Oxydation des Tolualloxasins II

Abstract: Unter gleichem Titel habe ich friiher I) iiber das primgre Oxydationsproduct des Tolualloxazine berichtet.Die Fortsetzuog der Untersuchung hat jetzt zu der Stammform der Reihe der Alloxazine gefiihrt, deren Gewinnung der Zweck der Arbeit war, und ich m6chte deshalb schoo jetzt iiber die bisherigen Resultate berichten, wenngleich das behandelte Oebiet im Einzelnen noch der Ausarbeitung bedarf.Wird das in der letzten Mittheilung a) beschriebene Kalk-oder Barytsalz der als primares Oxydationsproduct erhaltenen Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1947
1947
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…2,5−7 In 1894, Kuḧling described the first intentional synthesis of lumazine (3) in which benzo[g]pteridine, also known as alloxozine (4), was oxidized to lumazine-6,7-dicarboxylic acid, followed by thermal decarboxylation to generate the product 3. 8,9 Later, in 1901 and 1906, synthesis of the pteridine ring system 1 was also reported by Gabriel and Colman, 10 and Isay, 11 respectively.…”
Section: ■ Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…2,5−7 In 1894, Kuḧling described the first intentional synthesis of lumazine (3) in which benzo[g]pteridine, also known as alloxozine (4), was oxidized to lumazine-6,7-dicarboxylic acid, followed by thermal decarboxylation to generate the product 3. 8,9 Later, in 1901 and 1906, synthesis of the pteridine ring system 1 was also reported by Gabriel and Colman, 10 and Isay, 11 respectively.…”
Section: ■ Introductionmentioning
confidence: 81%
“…Lepteridine (8) was isolated from New Zealand ma ̅ nuka honey (derived from the nectar of Leptospermum scoparium) by Brimble et al, who also confirmed its structure by total synthesis. 31 Speer et al reported the replication of this isolation, along with 6,7-dimethyllumazine (9); the structures of both compounds were assigned using Xray crystallography. 32 New Zealand ma ̅ nuka honey is well known for its antibacterial activity and, as a result of its high cost and limited availability, is often the subject of honey fraud.…”
Section: ■ Simple Lumazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all the pteridines have well-developed acidic properties and are soluble in both alkalies and ammonia (13,23,24,48,49,105,108). Quantitative data are available for only two compounds, 2-amino-6-hydroxypteridinej whose pK, is 8.0, and 2-amino-6-hydroxy-8-pteridinecarboxylic acid, whose pK,'s are 3.9 and 7.7, respectively, for the first and second dissociations (2).…”
Section: A Gekeral Chemical Propertiesmentioning
confidence: 97%
“…Knowledge of the pteridines1 originated in the 1890's when Hopkins (30,31,32) published the results of his investigations on the wing pigments of the common English brimstone butterfly and the white cabbage butterfly. At about the same time, synthetic work by Kühling resulted in the first laboratory preparation of a substance with this nucleus (48). The relationship between these efforts was not clearly realized until 1940 (73,74,102), when the wing pigments, now known as "pterins" (88,108), of the butterflies investigated by Hopkins were shown by Wieland and his collaborators to be derived from the pteridine ring system.…”
Section: Introductionmentioning
confidence: 99%